Issues and interpretations of the ignition risk rised from mechanical sparks in explosive atmospheres - Jurca, Adrian; Vătavu, Niculina; Sicoi, Sorin; Lupu, Leonard; Păun, Florin (My University, 2009)
The potential explosive zones are those industrial areas where there is a risk to be produced a mixture of air with gas, vapors, mists or combustible dust which can be ignited by the different ignition sources, resulting explosions which can produce life losses. The metallic materials of the equipment case or their components, from industrial installation, can become ignition sources by mechanical sparks and/or hot surfaces. The authors had identified and analyzed the ignition capacity by mechanical sparks on the main metallic materials and had established original solutions to prevent ignition of the explosive atmospheres.

Potencjalne strefy wybuchu to te obszary przemysłowe, w których zagrożenie stwarzają mieszaniny powietrza i gazu, par, oparów bądź palne przewody, które mogą ulec zapaleniu z różnych przyczyn, powodując wybuchy i zagrożenie dla życia człowieka. Metalowe obudowy instalacji przemysłowych bądź ich części mogą stanowić źródła zapłonu (mechaniczna iskra i/lub gorące powierzchnie). Autorzy zidentyfikowali i przeanalizowali zdolność zapłonową mechanicznej iskry w przypadku podstawowych materiałów metalowych i opracowali oryginalne rozwiązania polegające na przeciwdziałaniu zapłonowi w warunkach atmosfery wybuchowej.
Zagadnienia i interpretacja zagrożenia pożarowego od iskry mechanicznej w warunkach atmosfery wybuchowej
Wiertnictwo, Nafta, Gaz
Keywords: mechanical sparks; ignition; iskra mechaniczna; explosive atmospheres; zapłon; atmosfera wybuchowa; explosion protection; ochrona przed wybucham